Impact of carbon nanotubes and graphene on immune cells - Orecchioni, Marco (BioMed Central, 2014)
It has been recently proposed that nanomaterials, alone or in concert with their specific biomolecular conjugates, can be used to directly modulate the immune system, therefore offering a new tool for the enhancement of immune-based therapies against infectious disease and cancer. Here, we revised the publications on the impact of functionalized carbon nanotubes (f-CNTs), graphene and carbon nanohorns on immune cells. Whereas f-CNTs are the nanomaterial most widely investigated, we noticed a progressive increase of studies focusing on graphene in the last couple of years. The majority of the works (56%) have been carried out on macrophages, following by lymphocytes (30% of the studies). In the case of lymphocytes, T cells were the most investigated (22%) followed by monocytes and dendritic cells (7%), mixed cell populations (peripheral blood mononuclear cells, 6%), and B and natural killer (NK) cells (1%). Most of the studies focused on toxicity and biocompatibility, while mechanistic insights on the effect of carbon nanotubes on immune cells are generally lacking. Only very recently high-throughput gene-expression analyses have shed new lights on unrecognized effects of carbon nanomaterials on the immune system. These investigations have demonstrated that some f-CNTs can directly elicitate specific inflammatory pathways. The interaction of graphene with the immune system is still at a very early stage of investigation. This comprehensive state of the art on biocompatible f-CNTs and graphene on immune cells provides a useful compass to guide future researches on immunological applications of carbon nanomaterials in medicine.